Bilingual Couples in Conversation (Volume 149) - Ang-Tschachtli, Silja (A. Francke Verlag, 2022)
This book provides a detailed linguistic analysis of the communication between highly proficient bilingual couples, each consisting of a native speaker of English and of Swiss German. Combining the accounts of ten couples on their language use with an analysis of their actual linguistic behaviour, several areas of the partners' speech and interaction were closely examined. These include their language choice and language mixing, attitudes, expression of emotions, swearing, as well as their humour and laughter. In addition, the influence of the bilinguals' mother tongue and gender on their language use was explored. Thus, the study provides valuable insights into the language practices of established bilingual couples, while also contributing to the fields of fluent late bilingualism and gender research.